Agricultural biotechnology: risks and opportunities for developing country food security. (1st January 2000) - Pinstrup-Andersen, Per; Cohen, Marc J.
Agricultural biotechnology presents opportunities for reducing poverty, food insecurity, child malnutrition, and natural resource degradation. Small farmers in developing countries are faced with many problems and constraints which biotechnology may assist. About 1.2 billion people, or one of every five humans, live in a state of absolute poverty, on the equivalent of US1 a day or less. Modern biotechnology is not a silver bullet for achieving food security, but, used in conjunction with traditional knowledge and conventional agricultural research methods, it may be a powerful tool. Policies must expand and guide research and technology development to solve problems of importance to poor people. Research should focus on crops relevant to small farmers and poor consumers in developing countries, such as bananas, cassava, yams, sweet potatoes, rice, maize, wheat, and millet, along with livestock. Labelling may also be needed to identify content for cultural and religious reasons or simply because consumers want to know about the contents of their food and the processes used to produce it. It is also urgent that global biosafety standards and local regulatory capacity be strengthened within developing countries.